Comprehensive Hospitals Nurses' Cognition on Palliative Care in Shandong Province, China: A Cross-Sectional Study - Hailing Yang; Meimei Shang; Chunhua Sun; Lihua Li; Chao Wang (Tehran University of Medical Sciences, 2021)
Background: Palliative care is an essential part of medical practice, however, it has developed slowly in China. We aimed to analyze the current situations of the cognition on palliative care among the nurses in Shandong Province, China. Methods: This was a cross sectional study. Investigation of 1050 nurses came from 5 third-class hospitals and 5 second-class hospitals in Shandong Province, China from Jul to Oct in 2018. The questionnaire included 4 parts: general information of the subject, the questionnaire of palliative nursing knowledge, attitude, and the behavior. Data were collected by the APP. Overall, after eliminating the invalid questionnaires, 1026 questionnaires were included in the final analyses. The software Stata 14.2 was used for all statistical analyses. Results: The score of knowledge and attitude was low, the practice was higher. Multivariate analysis results: the significant independent variables of univariate analysis were included in the multivariate non-conditional logistic regression model for analysis. Some departments had statistical significance in knowledge multivariate Logistic regression analysis. The multivariate logistic regression analysis of practice was significant for physical health and religious beliefs. The statistical variables of the total score of cognition were gender, age of care, health status and religious beliefs. Conclusion: Nursing knowledge is lacking and attitude remains to be improved as soon as possible. It is vital to improve the cognition of palliative care of nurses in Shandong general hospitals by developing relevant rules and regulations, strengthening the supervision of relevant ant departments, and enhancing training for nurses.